NATO as an actor of political communication - Arendarska, Justyna (Political Preferences, 2017)
The article raises the issue how the North Atlantic Treaty Organisation communicates with the broad public and how the organisation creates its image in the social media. The paper presents quantitative and qualitative content analysis of the communication that was published on the official NATO account on Twitter in the first three months of 2017. The aim of the study was to determine who is the main recipient of the communication, and what kind of language is used by the sender. In the main hypothesis author claims that the language and format of the communication does illustrate the effect of mediatization on communication processes in online media. The author proved that even the language and format of the communication on security issues are formatted according to the requirements of online media and thus, are affected by the mediatization processes. Key words: NATO, political communication, strategic communication, mediatization, social media